Arte, viagens e benzimento: etnografia da formação do artistaxamã João Kennedy Lima Barreto - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
This research addresses the ethnography of shamanic formation of a Tukano Indian, Bu'ú Kennedy, seeking to highlight the place of art, shamanism and the establishment of a network of circulation and sociability in their creative experience. The text discusses the concept of Art, Indigenous Art, from their experiences and perceptions, trying to think the expressions from a more guided study in daily life, travel and benzimentos [spiritual protection], not necessarily in the study of objects produced by Bu'ú. I present the context in which the artist is inserted, highlighting aspects of shamanism from the fieldwork carried out in Manaus (AM), Olivença (BA) Itabuna (BA), Japurá (AM), Vila Bittencourt (AM), São José do Apaporis Community (AM) and the Boca Traíra Community (Colômbia).
Keywords: Etnobiografia indígena; Antropologia da Arte; Xamanismo; CIÊNCIAS HUMANAS: ANTROPOLOGIA: ETNOLOGIA INDÍGENA